(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Glaucoma is a disease that is associated with elevated intraocular pressure. Most commonly, single active agent beta-adrenoceptor blockers (particularly, timolol-only preparations) are used as a first-line therapy for primary open-angle glaucoma (POAG). Purpose: To compare the efficacy of various timolol-only preparations available in the Ukrainian pharmaceutical market as a monotherapy for POAG on the basis of expert assessment. Methods: Forty-four ophthalmologists from various Ukrainian regions participated in the questionnaire survey. The participants varied in length of service, academic degree and experience in managing the disease. Survey data were processed using the method of the prior ranking of factors. Results: Mathematic modeling was used to construct the bar chart of ranks from the processed results of the survey. The overall impact of any factor on the examined variable was assessed through the sum of ranks. Conclusion: The method of the prior ranking of factors was used to establish that, in the opinion of the surveyed ophthalmologists, CUSIMOLOL, ARUTIMOL and OFTAN TIMOLOL are the three most efficient timolol-only preparations for the treatment of POAG.